2000
DOI: 10.1098/rstb.2000.0688
|View full text |Cite
|
Sign up to set email alerts
|

Fish otoliths: do sizes correlate with taxonomic group, habitat and/or luminescence?

Abstract: Otoliths are dense structures in the ears of fishes that function in hearing and gravity perception. Otolith (sagitta) diameters, as percentages of standard length (% SL), are calculated for 247 marine fish species in 147 families and compared by taxonomic group (usually order), habitat and presence or absence of luminescence. Otolith sizes range from 0.4-31.4 mm and 0.08-11.2% SL. The eel and spiny eel orders Anguilliformes and Notacanthiformes have small to very small otoliths, as do the triggerfish order Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 8 publications
3
88
0
Order By: Relevance
“…In addition to the environmental parameters (Aguirre and Lombarte 1999, Torres et al 2000, Volpedo and Echeverría 2000, Gauldie and Crampton 2002, Volpedo and Fuchs 2010, also other factors have effect on the otoliths, they include ontogenetic factors (Tombari et al 2005, Gonzalez Naya et al 2012, physiological factors as the hearing capabilities associated with specialization in acoustic communication (Popper and Fay 1993, Paxton 2000, Lombarte and Cruz 2007, and the phylogeny (Nolf and Tyler 2006). All of those could affect the morphology, the morphometry, and the microstructure of sagittae ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the environmental parameters (Aguirre and Lombarte 1999, Torres et al 2000, Volpedo and Echeverría 2000, Gauldie and Crampton 2002, Volpedo and Fuchs 2010, also other factors have effect on the otoliths, they include ontogenetic factors (Tombari et al 2005, Gonzalez Naya et al 2012, physiological factors as the hearing capabilities associated with specialization in acoustic communication (Popper and Fay 1993, Paxton 2000, Lombarte and Cruz 2007, and the phylogeny (Nolf and Tyler 2006). All of those could affect the morphology, the morphometry, and the microstructure of sagittae ).…”
Section: Discussionmentioning
confidence: 99%
“…This variability is especially true for the saccular otolith (sagitta) associated with the inner ear organ, sacculus, in non-ostariophsean fi shes (Platt andPopper 1981, Lombarte andCruz 2007). The morphological differences affect both the size and shape of the otoliths (Paxton 2000).…”
Section: Introductionmentioning
confidence: 99%
“…occurs in deeper waters in the Canary Islands and Madeira may be in order to avoid overlapping with the trophic niches of other trichiurids as well as other species, such as Promethichthys prometheus (Pajuelo et al, 2008). Previous studies have concluded that otolith size is related to the habitat and behaviour of species (Paxton, 2000;Tuset et al, 2003;Volpedo and Echevarría, 2003). In most cases, it has been demonstrated that an increase in the depth distribution of species that live below 1000 m also implies an increase in otolith size (Lombarte and Cruz, 2007;Schulz-Mirbach et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Otoliths, which are the most common hard structures used to age teleosts, were not located or removed from the weedy seadragons examined, even after microscopic examination of the cranium. Paxton (2000) suggested that elongate epipelagic species have very small otoliths as a result of excessive background noise in turbulent waters that would interfere with an acute sense of hearing. These organisms generally have large eyes to compensate for the lack of acute hearing (Paxton 2000).…”
Section: Somatic Growthmentioning
confidence: 99%
“…Paxton (2000) suggested that elongate epipelagic species have very small otoliths as a result of excessive background noise in turbulent waters that would interfere with an acute sense of hearing. These organisms generally have large eyes to compensate for the lack of acute hearing (Paxton 2000). Weedy seadragons have large welldeveloped eyes; therefore, a keen sense of hearing may not be as important for these ambush predators as precise vision, and as a result, otoliths may be absent or microscopic in weedy seadragons.…”
Section: Somatic Growthmentioning
confidence: 99%